1998
DOI: 10.1023/b:joss.0000033158.05927.3f
|View full text |Cite
|
Sign up to set email alerts
|

Convection and Diffusion in Patterns in Oscillated Granular Media

Abstract: Motions of individual particles within the stripe and square patterns formed in oscillated granular media are studied using numerical simulations. Our eventdriven molecular dynamics simulations yield standing wave patterns in good accord with those observed in experiments at the same frequency and acceleration amplitude. The patterns are subharmonic and so return to their initial macroscopic state after two external cycles. However, simulations reveal that individual particles do not return to their initial po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…We have found that the simulations quantitatively reproduce experiments on standing waves in oscillated granular media, producing the correct wave patterns and wavelengths [9] and secondary instabilities [4]. With the numerical simulation, we not only have access to experimentally unmeasurable quantities [10], but we also can study systems that are not experimentally realizable, allowing us to test both the assumptions and results of the granular kinetic theory. Once the constitutive relations have been tested and possibly enhanced through the use of particle simulations, direct comparison between continuum theory and laboratory experiment becomes possible.…”
Section: As a Result The Central Question Remains Openmentioning
confidence: 75%
See 2 more Smart Citations
“…We have found that the simulations quantitatively reproduce experiments on standing waves in oscillated granular media, producing the correct wave patterns and wavelengths [9] and secondary instabilities [4]. With the numerical simulation, we not only have access to experimentally unmeasurable quantities [10], but we also can study systems that are not experimentally realizable, allowing us to test both the assumptions and results of the granular kinetic theory. Once the constitutive relations have been tested and possibly enhanced through the use of particle simulations, direct comparison between continuum theory and laboratory experiment becomes possible.…”
Section: As a Result The Central Question Remains Openmentioning
confidence: 75%
“…In simulations of oscillated granular media, the results are not sensitively dependent on v a or β, and ǫ = 0.7 produces good agreement with experiment [4,9,10]. In addition to forestalling collapse, variation of e allows us to further probe granular kinetic theory, which assumes that e ≈ 1.…”
Section: Driven Granular Media Simulationsmentioning
confidence: 60%
See 1 more Smart Citation
“…Pattern formation in granular media can perhaps be described by continuum equations analogous to those used in fluid system [9][10][11], but the continuum equations remain largely untested by experiment. Aspects of granular patterns have been described using phenomenological models [12][13][14], but making the connection to real systems requires an understanding of granular media at a more microscopic level.…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of this model for the coefficient of restitution are discussed and demonstrated in Refs. [15,18,19,20,21,22]. We have set ǫ = 0.6, because this value gives the best agreement in terms of particle compaction observed in similarly agitated states in experiments with nylon balls and in our simulations.…”
Section: B System Parametersmentioning
confidence: 99%